Idiopathic gingival fibromatosis with asymmetrical presentation and electrosurgical management - Dilip Ganpat Pol; Tanya Marguerite Lobo; Samruddhi Dilip Pol (Wolters Kluwer Medknow Publications, 2016)
Idiopathic gingival fibromatosis is a rare genetically heterogeneous condition characterized by recurrent gingival enlargement without any identifiable cause. We report a case of 14-year-old female patient affected with sporadic, nonsyndromic, progressive gingival enlargement. It manifested more severely on the right side of the mouth with history of recurrence after prior conventional surgical excision. Electrosurgical resection of the enlargement was done, and overall patient management had a successful outcome along with achieving preservation of teeth with poor prognosis in the 2 years follow-up.